1996
DOI: 10.1074/jbc.271.41.25089
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of DNA Adducts by Human Nucleotide Excision Repair

Abstract: The mechanism by which mammalian nucleotide excision repair (NER) detects a wide range of base lesions is poorly understood. Here, we tested the ability of human NER to recognize bulky modifications that either destabilize the DNA double helix (acetylaminofluorene (AAF) and benzo[a]pyrene diol-epoxide (BPDE) adducts, UV radiation products) or induce opposite effects by stabilizing the double helix (8-methoxypsoralen (8-MOP), anthramycin, and CC-1065 adducts). We constructed plasmid DNA carrying a defined numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
148
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(164 citation statements)
references
References 53 publications
11
148
0
5
Order By: Relevance
“…Instead, the observed substrate versatility of the GGR pathway implies that its promiscuous initiator, XPC protein, acts by recognizing damage-induced distortions of the DNA helix rather than specific base modifications. In support of this hypothesis, it has been observed that the GGR system exhibits a general preference for base adducts that lower the melting temperature of double-stranded DNA [45], suggesting that XPC protein may detect the single-stranded character of damaged sites carrying bulky lesions. However, not in all cases the degree of duplex destabilization correlates with excision efficiency.…”
Section: The Molecular Basis For Substrate Versatilitymentioning
confidence: 88%
“…Instead, the observed substrate versatility of the GGR pathway implies that its promiscuous initiator, XPC protein, acts by recognizing damage-induced distortions of the DNA helix rather than specific base modifications. In support of this hypothesis, it has been observed that the GGR system exhibits a general preference for base adducts that lower the melting temperature of double-stranded DNA [45], suggesting that XPC protein may detect the single-stranded character of damaged sites carrying bulky lesions. However, not in all cases the degree of duplex destabilization correlates with excision efficiency.…”
Section: The Molecular Basis For Substrate Versatilitymentioning
confidence: 88%
“…Psoralen monoadducts and crosslinks are, at least in part, recognized and repaired by NER in human cells (39)(40)(41)(42)(43)(44)(45)(46). Psoralen monoadducts are somewhat helix-stabilizing, whereas crosslinks are helix-destabilizing (47,48). If XPA and RPA recognize helical distortions, then we would not expect a psoralen monoadduct to be recognized with the same efficiency as a psoralen crosslink.…”
Section: Discussionmentioning
confidence: 99%
“…44 Since a variety of lesions are recognized, it has been suggested that the NER factors do not recognize the lesion itself, but the local distortions in the DNA that are associated with the lesions. 15,[44][45][46] In this connection, we have shown recently that the human NER factor XPC/HR23B is the first mammalian NER factor that recognizes anti- [BP]-N 2 -dG lesions; this factor distinguishes between the BD (+)-cis-, and MG (+)-trans-and (−)-trans-[BP]-N 2 -dG lesions by opening the duplex to different extents and at different sites in the vicinity of the lesions. 47 Gunz et al have proposed a thermodynamic probing mechanism based on their observations that differences of more than 3 orders of magnitude are observed in the efficiency by which helix-destabilizing and helix-stabilizing adducts are excised by the NER mechanism.…”
Section: Dynamic Flexibility and Ner Damage Recognitionmentioning
confidence: 99%
“…47 Gunz et al have proposed a thermodynamic probing mechanism based on their observations that differences of more than 3 orders of magnitude are observed in the efficiency by which helix-destabilizing and helix-stabilizing adducts are excised by the NER mechanism. 15 According to their bipartite model of NER, the NER machinery first recognizes disruptions of Watson-Crick hydrogen bonding, followed by an unspecified second verification step that ensures that a chemically modified nucleobase is indeed present. 7,8,16,48,49 This has been called an "indirect readout mechanism" by Dip et al 48 Our detailed structural analyses based on MD simulations have previously provided further insights into the nature of DNA distortions that provoke NER susceptibility.…”
Section: Dynamic Flexibility and Ner Damage Recognitionmentioning
confidence: 99%
See 1 more Smart Citation